Preparation method of photoresponse Cu-coated Fe heterogeneous MOF energy storage material, photoresponse Cu-coated Fe heterogeneous MOF energy storage material and application of photoresponse Cu-coated Fe heterogeneous MOF energy storage material
By adopting core-shell structure design in MOF materials and introducing photosensitive ligands and surface plasma treatment, the challenges of existing MOF materials in the coordinated optimization of photoresponsiveness and electrochemical performance are solved, and the combination of efficient photoresponsiveness and excellent energy storage performance is achieved, which is suitable for a variety of cutting-edge applications.
Patent Information
- Application Number
- CN202411807259.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing MOF materials have challenges in the coordinated optimization of photoresponsiveness and electrochemical properties, especially MOF materials with a single metal center are difficult to achieve efficient electron transmission and excellent photoresponsiveness simultaneously.
Through innovative core-shell structure design, precise introduction of photosensitive ligands and coordinated optimization of surface plasma treatment, a new Cu@Fe heterogeneous MOF material with high efficiency photoresponsiveness and excellent energy storage performance has been developed.
The organic combination of photoresponse performance and energy storage performance is achieved. The material exhibits high specific capacitance, excellent rate performance and excellent cycling stability. It is suitable for photovoltaic-energy storage integrated systems, smart windows and other fields.
Smart Images

Figure BDA0005179591390000151 
Figure BDA0005179591390000152 
Figure BDA0005179591390000161
Abstract
Description
Technical Field
[0001] The present invention relates to the field of MOF energy storage technology, and in particular to a preparation method of a light-responsive Cu@Fe heterogeneous MOF energy storage material, a light-responsive Cu@Fe heterogeneous MOF energy storage material and applications thereof. Background Art
[0002] With the rapid development of renewable energy and the promotion of smart grids, efficient and multifunctional energy storage materials have become a research hotspot in the energy field. Metal-organic framework (MOF) materials have attracted much attention in the field of energy storage due to their high specific surface area, adjustable porosity and rich functionalization possibilities. However, traditional MOF materials still face many challenges in practical applications, especially in the synergistic optimization of photoresponse performance and electrochemical performance.
[0003] In the prior art, MOF materials with a single metal center often find it difficult to simultaneously achieve efficient electron transfer and excellent photoresponse performance. For example, copper-based MOFs such as HKUST-1 have good electron conductivity but lack significant photoresponse characteristics. Iron-based MOFs such as MIL-101(Fe) exhibit photocatalytic activity under certain conditions, but their electron transfer efficiency is relatively low. In addition, most MOF materials face the problem of insufficient structural stability during long-term cycles, which severely limits their application in practical energy storage devices.
[0004] Some researchers have tried to improve the comprehensive performance of MOF materials by mixing metal centers or subsequent functional modification. However, these methods often find it difficult to achieve the optimal synergy of the functions of each component and face challenges in maintaining the high specific surface area and regular pore structure of the material. In particular, how to achieve an organic combination of light response performance and energy storage performance without sacrificing the inherent advantages of MOF materials is still a technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention aims to solve the above technical problems and develop a new Cu@Fe heterogeneous MOF material with both high-efficiency light response performance and excellent energy storage performance through innovative core-shell structure design, precise introduction of photosensitive ligands and synergistic optimization of surface plasma treatment.
[0006] The object of the present invention is to provide a method for preparing a light-responsive Cu@Fe heterogeneous MOF energy storage material, comprising the following steps:
[0007] (1) Preparation of core copper-based MOF:
[0008] First, add 200-250 parts by weight of N,N-dimethylformamide into a 500 mL round-bottom flask;
[0009] Secondly, add 30-40 parts by weight of copper nitrate trihydrate and stir at 20-25°C until it is completely dissolved;
[0010] Then, slowly add 15-20 parts by weight of 1,3,5-benzenetricarboxylic acid and continue stirring for 30-60 minutes;
[0011] Again, the mixture is transferred into a polytetrafluoroethylene-lined autoclave and sealed;
[0012] Next, the reactor is placed in an oven at 120-140° C. for 24-48 hours;
[0013] Afterwards, the mixture was cooled to room temperature naturally, filtered, and washed with N,N-dimethylformamide and ethanol three times each;
[0014] Finally, the obtained product was dried under vacuum at 80-100°C for 12-24 hours to obtain the inner core copper-based MOF;
[0015] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0016] First, the core copper-based MOF obtained in step (1) is dispersed in 180-220 parts by weight of N,N-dimethylformamide and subjected to ultrasonic treatment for 30-60 minutes;
[0017] Secondly, dissolving 25-35 parts by weight of ferric chloride hexahydrate in 50-70 parts by weight of N,N-dimethylformamide;
[0018] Then, 8-12 parts by weight of terephthalic acid and 2-4 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid are dissolved in the remaining N,N-dimethylformamide;
[0019] Again, slowly drop the iron salt solution into the core copper-based MOF suspension and stir for 30-60 minutes;
[0020] Next, slowly add the mixed solution of terephthalic acid and 2,2'-bipyridine-5,5'-dicarboxylic acid, and stir at room temperature for 2-4 hours;
[0021] Afterwards, the resulting mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed;
[0022] Then, the reactor is placed in an oven at 150-180° C. for 48-72 hours;
[0023] Then, the mixture was cooled to room temperature naturally, filtered, and washed with N,N-dimethylformamide and ethanol three times each;
[0024] Finally, the obtained product was vacuum dried at 100-120°C for 24-48 hours to obtain the core-shell structure Cu@Fe-MOF;
[0025] (3) Surface plasma treatment:
[0026] First, the core-shell structure Cu@Fe-MOF obtained in step (2) is placed in a plasma treatment chamber;
[0027] Secondly, evacuate to 1-5Pa;
[0028] Then, oxygen is introduced and the pressure is controlled at 10-50Pa;
[0029] Again, set the RF power to 50-100W and the treatment time to 5-15 minutes;
[0030] Finally, turn off the power, vent to normal pressure, take out the sample, and obtain the photoresponsive Cu@Fe heterogeneous MOF energy storage material.
[0031] Preferably, the inner core copper-based MOF is HKUST-1.
[0032] Preferably, the shell of the core-shell structure Cu@Fe-MOF is MIL-101(Fe).
[0033] Preferably, the preparation process of the core copper-based MOF in step (1) is carried out in a polytetrafluoroethylene-lined high-pressure reactor.
[0034] Preferably, the preparation process of the core-shell structure Cu@Fe-MOF in step (2) is carried out in a polytetrafluoroethylene-lined high-pressure reactor.
[0035] Preferably, 2,2'-bipyridine-5,5'-dicarboxylic acid is added as a photosensitizing ligand in step (2).
[0036] Preferably, the plasma treatment in step (3) uses oxygen as the treatment gas.
[0037] Photoresponsive Cu@Fe heterogeneous MOF energy storage material, which is prepared by the method described.
[0038] Preferably, the material has a core-shell structure, wherein the core is a copper-based MOF and the shell is an iron-based MOF.
[0039] The photoresponsive Cu@Fe heterogeneous MOF energy storage material is used in supercapacitors.
[0040] The core innovation of the present invention lies in its unique molecular design and fine structural regulation. First, HKUST-1 is used as the core, and its abundant d-orbital electrons and strong π-d orbital interactions are used to construct an efficient electron transmission channel. Secondly, MIL-101(Fe) is selected as the shell, and by introducing 2,2'-bipyridine-5,5'-dicarboxylic acid as a photosensitive ligand, a significant enhancement of the light response performance is achieved. This core-shell structure not only achieves spatial separation of functions, but also forms a unique electronic state at the interface, further optimizing the electrochemical properties of the material.
[0041] More notably, the present invention significantly increases the active sites on the material surface while maintaining the integrity of the MOF skeleton through a carefully designed surface plasma treatment. This treatment not only improves the electrochemical activity of the material, but also may introduce oxygen vacancies or other defects on the MOF surface, further enhancing the material's light response performance and charge separation efficiency.
[0042] From the perspective of molecular orbital theory and solid physics, the core-shell structure of the present invention realizes energy band engineering at the molecular scale. The conduction band of the core HKUST-1 and the valence band of the shell MIL-101(Fe) form a step-like energy level structure, which is conducive to the rapid separation and directional migration of photogenerated electron-hole pairs. At the same time, the introduction of photosensitive ligands may form a coordination field splitting around Fe(III) ions, generate new energy levels, and thus broaden the light absorption range of the material.
[0043] In addition, the present invention also exhibits some unexpected technical effects. For example, the core-shell structure not only increases the specific surface area of the material, but also forms a unique microporous structure at the interface, which may be due to the mismatch effect of the two MOF lattices. This special pore structure provides an ideal channel for the rapid diffusion of the electrolyte, and may also serve as an active site for charge storage, thereby greatly improving the capacitance performance and rate performance of the material.
[0044] In general, the present invention successfully combines the photoresponsive function with the efficient energy storage performance through multiple synergistic effects, and develops a multifunctional, high-performance new MOF material. This material not only greatly surpasses the existing technology in various performance indicators, but also opens up new possibilities for the development of a new generation of intelligent and integrated energy storage devices. Its excellent photoelectric conversion efficiency, high specific capacitance, excellent rate performance and excellent cycle stability give it broad application prospects in many cutting-edge fields such as photovoltaic-energy storage integrated systems, smart windows, and wearable devices. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] This embodiment provides a photoresponsive Cu@Fe heterogeneous MOF energy storage material and a preparation method thereof. The material has a core-shell structure, with the core being HKUST-1 copper-based MOF and the shell being MIL-101(Fe) iron-based MOF. This unique structural design is intended to combine the advantages of two metal MOFs to achieve efficient electron transport and photoresponsive performance.
[0048] The preparation method of the material comprises the following steps:
[0049] (1) Preparation of core copper-based MOF (HKUST-1):
[0050] First, add 200 parts by weight of N,N-dimethylformamide to 500 mL of round-bottomed roasted melon. Secondly, add 30 parts by weight of copper nitrate trihydrate and stir at 20°C until completely dissolved. Then, slowly add 15 parts by weight of 1,3,5-benzenetricarboxylic acid and continue stirring for 30 minutes. Again, transfer the mixture to a polytetrafluoroethylene-lined autoclave and seal it. Next, place the reactor in a 120°C oven for 24 hours. After that, cool naturally to room temperature, filter, and wash 3 times each with N,N-dimethylformamide and ethanol. Finally, the resulting product was vacuum dried at 80°C for 12 hours to obtain a core copper-based MOF.
[0051] Preferably, in the embodiment of the present invention, HKUST-1 is selected based on its excellent electronic conductivity. This is because the strong interaction between the d orbital of the copper ion and the π orbital of the ligand is conducive to the rapid transmission of electrons in the MOF framework. This efficient electron transmission channel provides a good charge and discharge performance basis for the entire material.
[0052] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0053] First, the core copper-based MOF obtained in step (1) is dispersed in 180 parts by weight of N,N-dimethylformamide and ultrasonically treated for 30 minutes. Secondly, 25 parts by weight of ferric chloride hexahydrate are dissolved in 50 parts by weight of N,N-dimethylformamide. Then, 8 parts by weight of terephthalic acid and 2 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid are dissolved in the remaining N,N-dimethylformamide. Again, the iron salt solution is slowly added dropwise to the core copper-based MOF suspension and stirred for 30 minutes. Next, the mixed solution of terephthalic acid and 2,2'-bipyridine-5,5'-dicarboxylic acid is slowly added and stirred at room temperature for 2 hours. Thereafter, the resulting mixture is transferred to a polytetrafluoroethylene-lined autoclave and sealed. Subsequently, the autoclave is placed in an oven at 150°C and kept for 48 hours. Subsequently, it is naturally cooled to room temperature, filtered, and washed 3 times each with N,N-dimethylformamide and ethanol. Finally, the obtained product was dried in vacuum at 100 °C for 24 h to obtain the core-shell structured Cu@Fe-MOF.
[0054] It is worth noting that in this embodiment, the introduction of 2,2'-bipyridine-5,5'-dicarboxylic acid as a photosensitive ligand significantly enhances the light response performance of the material. This photosensitive ligand can form a photosensitive complex with iron ions under light conditions, promote the excitation and transfer of electrons, and thus improve the photoelectric conversion efficiency of the material.
[0055] (3) Surface plasma treatment:
[0056] First, the core-shell structure Cu@Fe-MOF obtained in step (2) is placed in a plasma treatment chamber. Secondly, the vacuum is evacuated to 1Pa. Then, oxygen is introduced and the pressure is controlled at 10Pa. Again, the RF power is set to 50W and the treatment time is 5 minutes. Finally, the power is turned off, the exhaust is reduced to normal pressure, and the sample is taken out to obtain the light-responsive Cu@Fe heterogeneous MOF energy storage material.
[0057] Furthermore, the plasma treatment step of the present invention is a key innovation. By using oxygen plasma treatment, the surface of the MOF can be effectively activated, the active sites can be increased, and the reactivity of the material can be improved. This treatment may introduce surface defects or change surface functional groups, thereby further enhancing the light response performance and electrochemical performance of the material.
[0058] Example 2
[0059] This embodiment also provides a photoresponsive Cu@Fe heterogeneous MOF energy storage material and a preparation method thereof, but some parameters are adjusted to explore the effects of different conditions on the material properties.
[0060] The preparation method of the material comprises the following steps:
[0061] (1) Preparation of core copper-based MOF (HKUST-1):
[0062] First, add 225 parts by weight of N,N-dimethylformamide to 500 mL of round-bottomed roasted melon. Secondly, add 35 parts by weight of copper nitrate trihydrate and stir at 22.5°C until completely dissolved. Then, slowly add 17.5 parts by weight of 1,3,5-benzenetricarboxylic acid and continue stirring for 45 minutes. Again, transfer the mixture to a polytetrafluoroethylene-lined autoclave and seal it. Next, place the reactor in a 130°C oven for 36 hours. Afterwards, cool naturally to room temperature, filter, and wash 3 times each with N,N-dimethylformamide and ethanol. Finally, the resulting product was vacuum dried at 90°C for 18 hours to obtain a core copper-based MOF.
[0063] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0064] First, the core copper-based MOF obtained in step (1) is dispersed in 200 parts by weight of N,N-dimethylformamide and ultrasonically treated for 45 minutes. Secondly, 30 parts by weight of ferric chloride hexahydrate are dissolved in 60 parts by weight of N,N-dimethylformamide. Then, 10 parts by weight of terephthalic acid and 3 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid are dissolved in the remaining N,N-dimethylformamide. Again, the iron salt solution is slowly added dropwise to the core copper-based MOF suspension and stirred for 45 minutes. Next, the mixed solution of terephthalic acid and 2,2'-bipyridine-5,5'-dicarboxylic acid is slowly added and stirred at room temperature for 3 hours. Thereafter, the resulting mixture is transferred to a polytetrafluoroethylene-lined autoclave and sealed. Subsequently, the autoclave is placed in an oven at 165°C and kept for 60 hours. Subsequently, it is naturally cooled to room temperature, filtered, and washed 3 times with N,N-dimethylformamide and ethanol each. Finally, the obtained product was vacuum dried at 110 °C for 36 h to obtain the core-shell structured Cu@Fe-MOF.
[0065] Preferably, in this embodiment, by extending the reaction time and increasing the reaction temperature, we expect to obtain a more complete core-shell structure and a higher crystallinity. This optimization may affect the specific surface area and porosity of the material, thereby affecting its energy storage performance.
[0066] (3) Surface plasma treatment:
[0067] First, the core-shell structure Cu@Fe-MOF obtained in step (2) is placed in a plasma treatment chamber. Secondly, evacuate to 3Pa. Then, introduce oxygen and control the pressure at 30Pa. Again, set the RF power to 75W and the treatment time to 10 minutes. Finally, turn off the power, exhaust to normal pressure, take out the sample, and obtain the light-responsive Cu@Fe heterogeneous MOF energy storage material.
[0068] It is worth noting that the intensity and time of plasma treatment were increased in this embodiment, which may lead to deeper surface modification and further enhance the photoresponse performance and electrochemical activity of the material.
[0069] Example 3
[0070] This example provides another photoresponsive Cu@Fe heterogeneous MOF energy storage material and a preparation method thereof, and further explores the effect of parameter adjustment on material properties.
[0071] The preparation method of the material comprises the following steps:
[0072] (1) Preparation of core copper-based MOF (HKUST-1):
[0073] First, add 250 parts by weight of N,N-dimethylformamide to 500 mL of round-bottomed roasted melon. Secondly, add 40 parts by weight of copper nitrate trihydrate and stir at 25°C until completely dissolved. Then, slowly add 20 parts by weight of 1,3,5-benzenetricarboxylic acid and continue stirring for 60 minutes. Again, transfer the mixture to a polytetrafluoroethylene-lined autoclave and seal it. Next, place the reactor in a 140°C oven for 48 hours. Afterwards, cool naturally to room temperature, filter, and wash 3 times each with N,N-dimethylformamide and ethanol. Finally, the resulting product was vacuum dried at 100°C for 24 hours to obtain a core copper-based MOF.
[0074] Furthermore, in this embodiment, by increasing the concentration of the reactants and extending the reaction time, we expect to obtain HKUST-1 crystals with higher yield and larger particle size, which may affect the formation process of the core-shell structure and the performance of the final material.
[0075] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0076] First, the core copper-based MOF obtained in step (1) is dispersed in 220 parts by weight of N,N-dimethylformamide and ultrasonically treated for 60 minutes. Secondly, 35 parts by weight of ferric chloride hexahydrate are dissolved in 70 parts by weight of N,N-dimethylformamide. Then, 12 parts by weight of terephthalic acid and 4 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid are dissolved in the remaining N,N-dimethylformamide. Again, the iron salt solution is slowly added dropwise to the core copper-based MOF suspension and stirred for 60 minutes. Next, the mixed solution of terephthalic acid and 2,2'-bipyridine-5,5'-dicarboxylic acid is slowly added and stirred at room temperature for 4 hours. Thereafter, the resulting mixture is transferred to a polytetrafluoroethylene-lined autoclave and sealed. Subsequently, the autoclave is placed in an oven at 180°C and kept for 72 hours. Subsequently, it is naturally cooled to room temperature, filtered, and washed 3 times each with N,N-dimethylformamide and ethanol. Finally, the obtained product was vacuum dried at 120 °C for 48 h to obtain the core-shell structured Cu@Fe-MOF.
[0077] It is worth noting that the amount of 2,2'-bipyridine-5,5'-dicarboxylic acid was increased in this embodiment, which may further enhance the photoresponse performance of the material. At the same time, extending the reaction time and increasing the reaction temperature may affect the integrity and crystallinity of the core-shell structure.
[0078] (3) Surface plasma treatment:
[0079] First, the core-shell structure Cu@Fe-MOF obtained in step (2) is placed in a plasma treatment chamber. Secondly, evacuate to 5Pa. Then, introduce oxygen and control the pressure at 50Pa. Again, set the RF power to 100W and the treatment time to 15 minutes. Finally, turn off the power, exhaust to normal pressure, take out the sample, and obtain the light-responsive Cu@Fe heterogeneous MOF energy storage material.
[0080] Preferably, the highest intensity plasma treatment is used in this embodiment, which may lead to significant changes in the surface of the material, including the introduction of more defect sites and functional groups, thereby significantly improving the electrochemical activity and photoresponse performance of the material.
[0081] Example 4
[0082] This embodiment provides a light-responsive Cu@Fe heterogeneous MOF energy storage material and a preparation method thereof, and explores the influence of intermediate parameter values on material properties.
[0083] The preparation method of the material comprises the following steps:
[0084] (1) Preparation of core copper-based MOF (HKUST-1):
[0085] First, add 225 parts by weight of N,N-dimethylformamide to 500 mL of round-bottomed roasted melon. Secondly, add 35 parts by weight of copper nitrate trihydrate and stir at 22.5°C until completely dissolved. Then, slowly add 17.5 parts by weight of 1,3,5-benzenetricarboxylic acid and continue stirring for 45 minutes. Again, transfer the mixture to a polytetrafluoroethylene-lined autoclave and seal it. Next, place the reactor in a 130°C oven for 36 hours. Afterwards, cool naturally to room temperature, filter, and wash 3 times each with N,N-dimethylformamide and ethanol. Finally, the resulting product was vacuum dried at 90°C for 18 hours to obtain a core copper-based MOF.
[0086] Furthermore, this embodiment adopts intermediate reaction parameters to balance factors such as yield, crystallinity and particle size to obtain the best core copper-based MOF structure. This balance may affect the subsequent formation of the core-shell structure and the performance of the final material.
[0087] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0088] First, the core copper-based MOF obtained in step (1) is dispersed in 200 parts by weight of N,N-dimethylformamide and ultrasonically treated for 45 minutes. Secondly, 30 parts by weight of ferric chloride hexahydrate are dissolved in 60 parts by weight of N,N-dimethylformamide. Then, 10 parts by weight of terephthalic acid and 3 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid are dissolved in the remaining N,N-dimethylformamide. Again, the iron salt solution is slowly added dropwise to the core copper-based MOF suspension and stirred for 45 minutes. Next, the mixed solution of terephthalic acid and 2,2'-bipyridine-5,5'-dicarboxylic acid is slowly added and stirred at room temperature for 3 hours. Thereafter, the resulting mixture is transferred to a polytetrafluoroethylene-lined autoclave and sealed. Subsequently, the autoclave is placed in an oven at 165°C and kept for 60 hours. Subsequently, it is naturally cooled to room temperature, filtered, and washed 3 times with N,N-dimethylformamide and ethanol each. Finally, the obtained product was vacuum dried at 110 °C for 36 h to obtain the core-shell structured Cu@Fe-MOF.
[0089] Preferably, in this embodiment, by selecting the reaction conditions of intermediate values, we expect to achieve the best balance between the integrity of the core-shell structure, crystallinity and photoresponsiveness. In particular, the amount of 2,2'-bipyridine-5,5'-dicarboxylic acid is selected as an intermediate value, aiming to achieve the best combination of photosensitivity and structural stability.
[0090] (3) Surface plasma treatment:
[0091] First, the core-shell structure Cu@Fe-MOF obtained in step (2) is placed in a plasma treatment chamber. Secondly, evacuate to 3Pa. Then, introduce oxygen and control the pressure at 30Pa. Again, set the RF power to 75W and the treatment time to 10 minutes. Finally, turn off the power, exhaust to normal pressure, take out the sample, and obtain the light-responsive Cu@Fe heterogeneous MOF energy storage material.
[0092] It is worth noting that a moderate intensity plasma treatment was used in this embodiment, which is intended to strike a balance between material surface activation and structural integrity. We expect that this treatment can moderately increase the surface active sites while avoiding excessive damage to the core-shell structure of the material.
[0093] Finally, it is worth emphasizing that these examples demonstrate the core innovation of the present invention: through the carefully designed core-shell structure, the introduction of photosensitive ligands and surface plasma treatment, the organic combination of light response performance and efficient energy storage performance is achieved. The development of this multifunctional MOF material provides new possibilities for solving the problem of energy storage and conversion, and is expected to find wide application in supercapacitors, photoelectric conversion devices and other fields.
[0094] Comparative Example 1: Single HKUST-1MOF Material
[0095] This comparative example aims to verify the necessity of the core-shell structure. HKUST-1 is prepared by the same method as in Example 1, but without subsequent core-shell structure construction and surface treatment.
[0096] The preparation method comprises the following steps:
[0097] First, 200 parts by weight of N,N-dimethylformamide were added to 500 mL of round-bottomed roasted melon. Secondly, 30 parts by weight of copper nitrate trihydrate were added and stirred at 20°C until completely dissolved. Then, 15 parts by weight of 1,3,5-benzenetricarboxylic acid were slowly added and stirring was continued for 30 minutes. Again, the mixture was transferred to a polytetrafluoroethylene-lined high-pressure reactor and sealed. Next, the reactor was placed in a 120°C oven for 24 hours. Afterwards, it was naturally cooled to room temperature, filtered, and washed 3 times each with N,N-dimethylformamide and ethanol. Finally, the resulting product was vacuum dried at 80°C for 12 hours to obtain the HKUST-1MOF material.
[0098] Preferably, by comparison with Example 1, we expect that this single MOF structure will lack photoresponsiveness and its energy storage capacity may also be lower. This comparison can highlight the important role of the core-shell structure in achieving multifunctionality.
[0099] Comparative Example 2: Cu@Fe-MOF material without photosensitive ligand
[0100] This comparative example is intended to verify the necessity of the photosensitizing ligand, and adopts a method similar to that of Example 2, but does not add 2,2'-bipyridine-5,5'-dicarboxylic acid when preparing the outer shell.
[0101] The preparation method comprises the following steps:
[0102] (1) Preparation of core copper-based MOF (HKUST-1):
[0103] Same as step (1) of Example 2.
[0104] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0105] First, the core copper-based MOF obtained in step (1) is dispersed in 200 parts by weight of N,N-dimethylformamide and ultrasonically treated for 45 minutes. Secondly, 30 parts by weight of ferric chloride hexahydrate are dissolved in 60 parts by weight of N,N-dimethylformamide. Then, 13 parts by weight of terephthalic acid are dissolved in the remaining N,N-dimethylformamide. Again, the iron salt solution is slowly added dropwise to the core copper-based MOF suspension and stirred for 45 minutes. Next, the terephthalic acid solution is slowly added and stirred at room temperature for 3 hours. The subsequent steps are the same as in Example 2.
[0106] (3) Surface plasma treatment:
[0107] Same as step (3) of Example 2.
[0108] Furthermore, by comparing the performance difference between this comparative example and Example 2, we expect to clearly confirm the key role of 2,2'-bipyridine-5,5'-dicarboxylic acid as a photosensitive ligand in enhancing the photoresponsive performance of the material. This comparison can reveal the synergistic mechanism between the photosensitive ligand and the iron-based MOF.
[0109] Comparative Example 3: Cu@Fe-MOF material without plasma treatment
[0110] This comparative example is intended to verify the necessity of surface plasma treatment. The core-shell structure Cu@Fe-MOF is prepared by the same method as Example 3, but the final plasma treatment step is not performed.
[0111] The preparation method comprises the following steps:
[0112] (1) Preparation of core copper-based MOF (HKUST-1):
[0113] Same as step (1) of Example 3.
[0114] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0115] Same as step (2) of Example 3.
[0116] Preferably, by comparing the performance difference between this comparative example and Example 3, we expect to clearly confirm the important role of plasma treatment in enhancing the surface activity of the material, improving the photoresponse performance and electrochemical performance. This comparison can reveal how surface treatment affects the electronic structure and reactivity of the material.
[0117] Comparative Example 4: Inverse core-shell structure Fe@Cu-MOF material
[0118] This comparative example is intended to verify the necessity of a specific core-shell structure design, and a method similar to that of Example 4 is used, but the order of the materials of the core and the shell is reversed.
[0119] The preparation method comprises the following steps:
[0120] (1) Preparation of core iron-based MOF (MIL-101(Fe)):
[0121] First, add 200 parts by weight of N,N-dimethylformamide to 500 mL of round-bottomed roasted melon. Secondly, add 30 parts by weight of ferric chloride hexahydrate and stir at 22.5°C until completely dissolved. Then, slowly add 10 parts by weight of terephthalic acid and 3 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid, and continue stirring for 45 minutes. Again, transfer the mixture to a polytetrafluoroethylene-lined autoclave and seal it. Next, place the reactor in a 165°C oven and keep it for 60 hours. After that, cool naturally to room temperature, filter, and wash with N,N-dimethylformamide and ethanol 3 times each. Finally, the resulting product was vacuum dried at 110°C for 36 hours to obtain an inner core iron-based MOF.
[0122] (2) Preparation of core-shell structure Fe@Cu-MOF:
[0123] A similar procedure to step (2) of Example 4 was used, but the roles of the copper salt and the iron salt were interchanged.
[0124] (3) Surface plasma treatment:
[0125] Same as step (3) of Example 4.
[0126] Further, by comparing the performance difference between this comparative example and Example 4, we expect to confirm the importance of a specific core-shell structure design (copper-based core, iron-based shell) in achieving efficient electron transport and photoresponse performance. This comparison can reveal the intrinsic connection between material structure and performance.
[0127] Comparative Example 5: Cu / Fe mixed MOF material without core-shell structure
[0128] This comparative example aims to verify the superiority of the core-shell structure over the simple mixed structure, and a mixed MOF containing copper and iron is synthesized simultaneously by a one-step method.
[0129] The preparation method comprises the following steps:
[0130] First, 225 parts by weight of N,N-dimethylformamide were added to 500 mL of round-bottomed roasted melon. Secondly, 17.5 parts by weight of copper nitrate trihydrate and 15 parts by weight of ferric chloride hexahydrate were added and stirred at 22.5°C until completely dissolved. Then, a mixture of 13.75 parts by weight of 1,3,5-benzenetricarboxylic acid, 5 parts by weight of terephthalic acid and 1.5 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid was slowly added and continued to stir for 45 minutes. Again, the mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed. Next, the reactor was placed in an oven at 150°C for 48 hours. Afterwards, it was naturally cooled to room temperature, filtered, and washed 3 times each with N,N-dimethylformamide and ethanol. Finally, the resulting product was vacuum dried at 100°C for 24 hours to obtain a Cu / Fe mixed MOF material.
[0131] Then, the same surface plasma treatment as in Example 4 was performed.
[0132] Preferably, by comparing the performance difference between this comparative example and Example 4, we expect to confirm the superiority of the core-shell structure in achieving functional partitioning, improving electron transfer efficiency and enhancing light response performance. This comparison can reveal how the core-shell structure synergistically exerts the respective advantages of the core and the shell.
[0133] Comparative Example 6: Cu@Fe-MOF materials with different photosensitive ligand contents
[0134] This comparative example aims to verify the optimization effect of the content of the photosensitizing ligand, and adopts a method similar to that of Example 1, but significantly increases the amount of 2,2'-bipyridine-5,5'-dicarboxylic acid.
[0135] The preparation method comprises the following steps:
[0136] (1) Preparation of core copper-based MOF (HKUST-1):
[0137] Same as step (1) of Example 1.
[0138] (2) Preparation of core-shell structure Cu@Fe-MOF:
[0139] First, the core copper-based MOF obtained in step (1) was dispersed in 180 parts by weight of N,N-dimethylformamide and ultrasonically treated for 30 minutes. Secondly, 25 parts by weight of ferric chloride hexahydrate was dissolved in 50 parts by weight of N,N-dimethylformamide. Then, 4 parts by weight of terephthalic acid and 6 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid were dissolved in the remaining N,N-dimethylformamide. The subsequent steps were the same as in Example 1.
[0140] (3) Surface plasma treatment:
[0141] Same as step (3) of Example 1.
[0142] Furthermore, by comparing the performance difference between this comparative example and Example 1, we expect to confirm the effect of optimizing the content of photosensitive ligands on material properties. Too high a content of photosensitive ligands may affect the structural stability of MOF, thereby affecting its overall performance. This comparison can reveal the balance between the content of photosensitive ligands and the structure and performance of the material.
[0143] We designed a series of comprehensive test experiments to evaluate the effectiveness and superiority of the photoresponsive Cu@Fe heterogeneous MOF energy storage material and its preparation method. These tests cover the structural characteristics, photoresponsive performance, electrochemical performance, and energy storage performance of the material, aiming to fully demonstrate the core innovations and unique advantages of the present invention.
[0144] First, we performed structural characterization of the materials. X-ray diffraction (XRD) analysis was used to confirm the crystal structure of HKUST-1 and MIL-101(Fe) and their presence in the core-shell material. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis were used to observe the morphology and interface characteristics of the core-shell structure. X-ray photoelectron spectroscopy (XPS) analysis was used to study the elemental composition and chemical state of the material surface, especially the changes before and after plasma treatment.
[0145] Secondly, we evaluated the photoresponse properties of the materials. UV-visible diffuse reflectance spectroscopy was used to analyze the light absorption characteristics of the materials. Photocurrent density measurements were performed under simulated sunlight irradiation to evaluate the photoelectric conversion efficiency of the materials. Transient photocurrent response tests were used to study the electron-hole pair separation efficiency of the materials under light conditions.
[0146] Thirdly, we studied the electrochemical properties of the materials in depth. Cyclic voltammetry (CV) tests were performed at different scan rates to evaluate the capacitance performance and reaction reversibility of the materials. Electrochemical impedance spectroscopy (EIS) analysis was used to study the electronic and ion transport properties of the materials. Constant current charge and discharge tests were performed at different current densities to evaluate the specific capacity and rate performance of the materials.
[0147] Finally, we performed long-term cyclic stability tests to evaluate the durability of the materials in practical applications.
[0148] All tests were conducted at room temperature (25±2°C) and relative humidity of 50±5%. The electrochemical test used a three-electrode system, with the working electrode being the prepared MOF material, the counter electrode being a platinum sheet, the reference electrode being a saturated calomel electrode (SCE), and the electrolyte being a 1M Na2SO4 aqueous solution.
[0149] Based on the above tests, we obtained the following results:
[0150] Table 1: Material structure and light response performance test results
[0151]
[0152] Table 2: Electrochemical performance and energy storage performance test results
[0153]
[0154]
[0155] According to the above test results, Example 3 exhibits the best comprehensive performance and can be regarded as the best embodiment of the present invention. It has the highest specific surface area (1720m 2 / g), maximum photocurrent density (18.7μA / cm 2 ), the fastest photoresponse time (63ms), the highest specific capacitance (390F / g), and the best cycling stability (96% retention after 5000 cycles).
[0156] After in-depth analysis of these data, we found that the present invention exhibits some unexpected technical effects:
[0157] 1. Ultra-high specific surface area and excellent pore structure: The specific surface area of Example 3 reaches 1720m 2 / g, which is much higher than that of single HKUST-1 (Comparative Example 1) and simple mixed MOF (Comparative Example 5). This significant improvement may be due to the interface effect of the core-shell structure, which forms an additional microporous structure at the contact surface of the two MOFs. This unique pore structure not only provides more active sites, but also facilitates the rapid diffusion of the electrolyte, thereby greatly improving the electrochemical performance of the material.
[0158] 2. Significantly enhanced photoresponse performance: The photocurrent density of Example 3 (18.7 μA / cm2) is more than 20 times higher than that of single HKUST-1 (Comparative Example 1, 0.8 μA / cm2). This huge improvement is not just a simple material combination effect, but comes from the synergistic effect of the photosensitive ligands in the core-shell structure and the surface activation brought about by plasma treatment. In particular, the photoresponse time is shortened to 63 ms, indicating that the material has extremely fast photoelectric conversion ability, which is of great significance for the development of efficient photoelectrochemical devices.
[0159] 3. Excellent rate performance: At a high current density of 20A / g, Example 3 still maintains 85% of the capacitance. This excellent rate performance is due to the synergistic effect of the core-shell structure. The core HKUST-1 provides a fast electron transmission channel, while the shell MIL-101 (Fe) provides an efficient ion diffusion pathway. This unique structural design achieves the synergistic optimization of electron and ion transmission, which is difficult to achieve with traditional single MOF materials.
[0160] 4. Excellent cycle stability: After 5000 cycles, Example 3 still maintains 96% of the capacitance. This excellent stability may be attributed to the protective effect of the core-shell structure. The outer shell MIL-101 (Fe) may play the role of a buffer layer during the cycle, reducing the structural stress of the inner core HKUST-1, thereby improving the stability of the overall material.
[0161] 5. Low charge transfer resistance: The charge transfer resistance of Example 3 is only 2.7Ω, which is much lower than that of other samples. This shows that the core-shell structure and plasma treatment greatly improve the conductivity and electrochemical activity of the material. In particular, this low resistance property is achieved while maintaining a high specific surface area, which is difficult to achieve with traditional porous materials.
[0162] In summary, the light-responsive Cu@Fe heterogeneous MOF energy storage material of the present invention exhibits a multi-faceted synergistic effect, not only greatly surpassing the single-component material in various performance indicators, but also realizing the organic combination of light-responsive performance and energy storage performance. This multifunctional, high-performance new material opens up new possibilities for the development of the next generation of intelligent energy storage devices, and is expected to find wide application in photovoltaic-energy storage integrated systems, smart windows and other fields.
[0163] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. Preparation method of light-responsive Cu@Fe heterogeneous MOF energy storage material, characterized in that , including the following steps: (1) Preparation of core copper-based MOF: First, add 200-250 parts by weight of N,N-dimethylformamide into a 500 mL round-bottom flask; Secondly, add 30-40 parts by weight of copper nitrate trihydrate and stir at 20-25°C until it is completely dissolved; Then, slowly add 15-20 parts by weight of 1,3,5-benzenetricarboxylic acid and continue stirring for 30-60 minutes; Again, the mixture is transferred into a polytetrafluoroethylene-lined autoclave and sealed; Next, the reactor is placed in an oven at 120-140° C. for 24-48 hours; Afterwards, the mixture was cooled to room temperature naturally, filtered, and washed with N,N-dimethylformamide and ethanol three times each; Finally, the obtained product was dried under vacuum at 80-100°C for 12-24 hours to obtain the inner core copper-based MOF; (2) Preparation of core-shell structure Cu@Fe-MOF: First, the core copper-based MOF obtained in step (1) is dispersed in 180-220 parts by weight of N,N-dimethylformamide and subjected to ultrasonic treatment for 30-60 minutes; Secondly, dissolving 25-35 parts by weight of ferric chloride hexahydrate in 50-70 parts by weight of N,N-dimethylformamide; Then, 8-12 parts by weight of terephthalic acid and 2-4 parts by weight of 2,2'-bipyridine-5,5'-dicarboxylic acid are dissolved in the remaining N,N-dimethylformamide; Again, slowly drop the iron salt solution into the core copper-based MOF suspension and stir for 30-60 minutes; Next, slowly add the mixed solution of terephthalic acid and 2,2'-bipyridine-5,5'-dicarboxylic acid, and stir at room temperature for 2-4 hours; Afterwards, the resulting mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed; Then, the reactor is placed in an oven at 150-180° C. for 48-72 hours; Then, the mixture was cooled to room temperature naturally, filtered, and washed with N,N-dimethylformamide and ethanol three times each; Finally, the obtained product was vacuum dried at 100-120°C for 24-48 hours to obtain the core-shell structure Cu@Fe-MOF; (3) Surface plasma treatment: First, the core-shell structure Cu@Fe-MOF obtained in step (2) is placed in a plasma treatment chamber; Secondly, vacuum to 1-5Pa; Then, oxygen is introduced and the pressure is controlled at 10-50Pa; Again, set the RF power to 50-100W and the treatment time to 5-15 minutes; Finally, turn off the power, vent to normal pressure, take out the sample, and obtain the photoresponsive Cu@Fe heterogeneous MOF energy storage material.
2. The preparation method according to claim 1, characterized in that , the core copper-based MOF is HKUST-1.
3. The preparation method according to claim 1, characterized in that , the shell of the core-shell structure Cu@Fe-MOF is MIL-101(Fe).
4. The preparation method according to claim 1, characterized in that The preparation process of the core copper-based MOF in step (1) is carried out in a polytetrafluoroethylene-lined high-pressure reactor.
5. The preparation method according to claim 1, characterized in that ,The preparation process of the core-shell structure Cu@Fe-MOF described in step (2) is carried out in a high-pressure reactor lined with polytetrafluoroethylene.
6. The preparation method according to claim 1, characterized in that , in step (2), 2,2'-bipyridine-5,5'-dicarboxylic acid is added as a photosensitizing ligand.
7. The preparation method according to claim 1, characterized in that , the plasma treatment described in step (3) uses oxygen as the processing gas.
8. A photoresponsive Cu@Fe heterogeneous MOF energy storage material, characterized in that , the material is prepared by the method described in any one of claims 1-7.
9. The light-responsive Cu@Fe heterogeneous MOF energy storage material according to claim 8, characterized in that ,The material has a core-shell structure, wherein the core is a copper-based MOF and the shell is an iron-based MOF.
10. Use of the photoresponsive Cu@Fe heterogeneous MOF energy storage material according to claim 8 or 9 in a supercapacitor.
Citation Information
Patent Citations
Method for preparing metal organic framework material based on discharge plasma in liquid phase
CN105037404A
Chiral ligand exchange type COF-coated MOF / L composite material and preparation method thereof
CN112604659A
Preparation method of double-MOF / biomass-based multifunctional composite material
CN113831749A
MIL-101 (Cr) (at) MOF-867 core-shell material as well as preparation method and application thereof
CN115041234A
Method for synchronously realizing rapid carbonization of MOF (Metal Organic Framework) array and rapid self-generation of CNTs (Carbon Nanotubes) on surface
CN116947023A